The Factors Contributing to the Social Inequality among the Community of Ranto Panyang Timur, West Aceh - Arfriani Maifizar; Sopar Sopar; Erizar Erizar; Fenecia Fenecia; Mahamadaree Waeno (JSW (Jurnal Sosiologi Walisongo), 2022)
Social processes that result in social migration often result in various social problems, such as disintegration between local residents and immigrants, which in the end leads to social inequality between local residents and immigrants. With the context of the research in the village of Ranto Panyang Timur Aceh Barat District, and applying descriptive qualitative this study indicated that the process of social inequality in the coastal fishermen community at Ranto Panyang Timur Village proceed since they came to that village, and the forms of the inequality are the neglect and discrimination in the context of social treatment and service from Keuchik (the head of the village) and his official staff. The factors that affect the social inequality between the indigenous residents and the fisherman who were relocated at Ranto Panyang Timur Village, West Aceh Regency were the least committed Keuchik’s, unresponsive village officials, and unfair treatment by the village officials in terms of services, and provide aid to the people who were relocated at Ranto Panyang Timur Village.